Navigation-Guided Transnasal Endoscopic Delineation of the Posterior Margin for Maxillary Sinus Cancers: A Preclinical Study - Taboni, Stefano; Ferrari, Marco; Daly, Michael J.; Chan, Harley H. L.; Eu, Donovan; Gualtieri, Tommaso; Jethwa, Ashok R.; Sahovaler, Axel; Sewell, Andrew; Hasan, Wael; Berania, Ilyes; Qiu, Jimmy; et al. (Frontiers in Oncology, 2021)
Background The resection of advanced maxillary sinus cancers can be challenging due to the anatomical proximity to surrounding critical anatomical structures. Transnasal endoscopy can effectively aid the delineation of the posterior margin of resection. Implementation with 3D-rendered surgical navigation with virtual endoscopy (3D-SNVE) may represent a step forward. This study was aimed to demonstrate and quantify the benefits of this technology. Material and Method Four maxillary tumors models with critical posterior extension were created in 4 artificial skulls (Sawbones®). Images were acquired with cone-beam computed tomography and tumor and carotid were contoured. Eight head-and-neck surgeons were recruited for the simulations. Surgeons delineated the posterior margin of resection through a transnasal approach and avoided the carotid while establishing an adequate resection margin with respect to tumor extirpation. Three simulations were performed: 1) unguided: based on pre-simulation study of cross-sectional imaging; 2) tumor-guided: guided by real-time tool tracking with 3D tumor and carotid rendering; 3) carotid-guided: tumor-guided with a 2-mm alert cloud surrounding the carotid. Distances of planes from carotid and tumor were classified as follows and points of the plane were classified accordingly: ““red”: through the carotid artery; “orange”: <2mm from the carotid; “yellow”: >2mm from the carotid and within the tumor or <5mm from tumor; “green”: >2mm from the carotid and 5-10mm from tumor; “blue”: >2mm from carotid and >10mm from tumor. The three techniques (unguided, tumour-guided and carotid-guided) were compared. Results 3D-SNVE for the transnasal delineation of the posterior margin in maxillary tumor models significantly improved the rate of margin-negative clearance around the tumor and reduced carotid artery damage. “Green” cuts occurred 52.4% in the unguided setting versus 62.1% and 64.9% in the tumor- and carotid-guided setting, respectively (p<.0001). “Red” cuts occurred 6.7% of the time in the unguided setting versus 0.9% and 1.0% in the tumor- and carotid-guided settings, respectively (p<.0001). Conclusions This preclinical study has demonstrated that 3D-SNVE provides a substantial improvement of the posterior margin delineation in terms of safety and oncological adequacy. Translation into the clinical setting, with a meticulous assessment of the oncological outcomes, will be the proposed next step.